Structural Transformation Patterns and Factors That Influenced: The Case In Indonesia - Hendarmin, Hendarmin; Wahyudi, Setyo Tri (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2023)
The purpose of this study is to determine the pattern of structural transformation and analyze the effect of per capita income, population, and human capital structural transformation in Indonesia. The research data uses data from three economic sectors, namely the agricultural, industrial, and service sectors in Indonesia from 1990-2019. The research analysis method is descriptive qualitative to see sectoral patterns and trends, while the quantitative analysis method uses the Chenery-Syrquin regression model approach. The findings in the study that there has been a structural transformation in Indonesia during the last three decades with the S-I-A pattern (agricultural service industry). The population has a positive and significant effect on the agricultural, industrial, and service sectors, while human capital has a significant positive effect on the industrial and service sectors. In conclusion, various factors influence structural transformation in different sectors in Indonesia.